ANALISIS LAJU KOROSI PADA BAJA ASTM A36 DENGAN VARIASI TEMPERATUR DAN WAKTU PERENDAMAN DALAM ALIRAN AIR LAUT - Marthiana, Wenny; Hamdani , Yacob (Teknosia, 2024)
Abstract: Technological developments in the maritime industry are increasing rapidly, but the problem of corrosion is a problem that still often occurs due to factors such as temperature, humidity and chemical content in the air. The most widely used metal in the maritime industry, especially in ship hulls, is ASTM A36 steel which is a low carbon steel. The purpose of this study was to determine variations in temperature and immersion time on the corrosion rate of ASTM A36 steel. In immersion using variations of immersion time of 24, 72 and 120 hours. With temperature variations of 29oC, 32oC and 35oC. The results of the study showed that the highest corrosion rate value occurred in ASTM A36 steel which was soaked at 35c which showed a corrosion rate value of 25.1965 mmpy (24 hours), 30.9557 mmpy (72 hours), 41.3223 mmpy (120 hours). then in the test sample material pitting corrosion and erosion corrosion occur. The results of this study show that high temperatures can accelerate the rate of corrosion in the marine environment.